Antioxidant and antidiabetic activity and phytoconstituents of lichen extracts with temperate and polar distribution - Torres-Benítez, Alfredo; Ortega-Valencia, José Erick; Jara-Pinuer, Nicolás; Sanchez, Marta; Vargas-Arana, Gabriel; Gómez-Serranillos, María Pilar; Simirgiotis, Mario J. (Frontiers in Pharmacology, 2023)
The objective of this research was to characterize the chemical composition of ethanolic extracts of the lichen species Placopsis contortuplicata, Ochrolechia frigida, and Umbilicaria antarctica, their antioxidant activity and enzymatic inhibition through in vitro and molecular docking analysis. In total phenol content, FRAP, ORAC, and DPPH assays, the extracts showed significant antioxidant activity, and in in vitro assays for inhibition of pancreatic lipase, α-glucosidase and α-amylase enzymes together with in silico studies for prediction of pharmacokinetic properties, toxicity risks and intermolecular interactions of compounds, the extracts evidenced inhibitory potential. Thirteen compounds were identified by UHPLC-ESI-QTOF-MS in P. contortuplicata, eighteen compounds in O. frigida, and twelve compounds in U. antarctica This study contributes to the knowledge of the pool of bioactive compounds present in lichens of temperate and polar distribution, and biological characteristics that increase interest in the discovery of natural products that offer alternatives for treatment studies of diseases related to oxidative stress and metabolic syndrome.